تأثير استخدام وسيلة الكلمات المتقاطعة في تدريس المفردات: دراسة تجريبية في المدرسة لقمان الإيتدائية الإسلامية المتكاملة بادنج - Ritonga, Tipa Nawati; Yufni Faisol; Hanomi (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2024)
The aim of this research is to reveal the influence of crossword puzzle media on the Arabic vocabulary skills of students in SDIT Luqman Padang. As for its research approach, it is a quantitative approach using experimental research methods based on field research. Data collection tools are tests, observations, interviews, and documents. The method of data analysis that researchers use is quantitative data analysis with the help of the SPSS 26 program. The results of the study were: 1) The ability of students to learn vocabulary appears from the average pre-test scores in the control class of 71.85 with the category "acceptable" and in the experimental class of 73.65 with the category "acceptable." 2) The use of crossword puzzle media to teach vocabulary consists of three stages: preliminary, primary, and final activities. 3) The impact of using crossword puzzle media in the teaching of vocabulary is acceptable. This statement emerged from the test results of an independent hypothesis sample t-test with a value of 0.000 less than 0.05, meaning Ha was accepted and Ho was rejected. Therefore, the researchers concluded that there was an influence on the use of crossword puzzle media in improving the Arabic vocabulary skills of fourth-grade students at the SDIT Luqman Padang.